2017
DOI: 10.1007/s00109-017-1510-z
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinase-14 triggers an anti-inflammatory proteolytic cascade in endotoxemia

Abstract: • MMP-14 levels decrease in lungs from endotoxemic mice and serum from septic patients. • Mmp14 mice show increased lung injury and mortality following endotoxemia. • Absence of Mmp14 decreases activated MMP-2 and increases S100A9 levels in lung tissue. • MMP-14 ameliorates inflammation by promoting S100A9 cleavage by activated MMP-2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 37 publications
1
24
0
Order By: Relevance
“…Apln + ECs may play an anti-inflammatory role required to maintain a balanced BM microenvironment. Apln + ECs show enriched expression of anti-inflammatory factors such as Mmp, Tgfb2, Nos3, and Ptgis (Aguirre et al, 2017;Bougaki et al, 2010;Jin et al, 2014;Manicone and McGuire, 2008;Dorris and Peebles, 2012;Knudsen et al, 1986). Accordingly, ablation of Apln + ECs leads to an increase of PB myeloid cells, which is a hallmark of numerous conditions with compromised BM function including aging, inflammation, or compromised stromal support (Kusumbe et al, 2016;Mann et al, 2018;Pietras, 2017;Tikhonova et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Apln + ECs may play an anti-inflammatory role required to maintain a balanced BM microenvironment. Apln + ECs show enriched expression of anti-inflammatory factors such as Mmp, Tgfb2, Nos3, and Ptgis (Aguirre et al, 2017;Bougaki et al, 2010;Jin et al, 2014;Manicone and McGuire, 2008;Dorris and Peebles, 2012;Knudsen et al, 1986). Accordingly, ablation of Apln + ECs leads to an increase of PB myeloid cells, which is a hallmark of numerous conditions with compromised BM function including aging, inflammation, or compromised stromal support (Kusumbe et al, 2016;Mann et al, 2018;Pietras, 2017;Tikhonova et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Blocking CALR activity attenuated murine acute lung injury by inducing polarization of M2 subtype macrophages, which are anti-inflammatory 57 . MMP14 was shown to trigger the anti-inflammatory proteolytic cascade to prevent lung injury in mice 58 . Interestingly, so far only a few studies have reported some biological functions of CGP-60474 59 61 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we have demonstrated that the matrix metalloproteinase MMP14 expression levels are strongly increased in the AT of obese mice ( Li and Zhao, 2020 ). Application of LPS substantially reduced the expression level of MMP14 in lungs; moreover, MMP14 -/- mice receiving LPS demonstrated 100% mortality connected with severe lung injury ( Aguirre et al, 2017 ). At the same time, MMP14 is strongly involved in amelioration of inflammation induced by endotoxins ( Aguirre et al, 2017 ).…”
Section: The Role Of the Angiotensin System For The Integral Viral Lomentioning
confidence: 99%
“…Application of LPS substantially reduced the expression level of MMP14 in lungs; moreover, MMP14 -/- mice receiving LPS demonstrated 100% mortality connected with severe lung injury ( Aguirre et al, 2017 ). At the same time, MMP14 is strongly involved in amelioration of inflammation induced by endotoxins ( Aguirre et al, 2017 ). Remarkably, ACE2 KO mice exacerbate Ang II-mediated inflammation and myocardial injury via substantial overexpression of MMP2, −9 and −14 ( Song et al, 2013 ), which can strongly degrade the extracellular and perivascular matrix.…”
Section: The Role Of the Angiotensin System For The Integral Viral Lomentioning
confidence: 99%